Bolsa Família, its design, its impacts and possibilities for the future - Sergei Suarez Dillon Soares (International Policy Centre for Inclusive Growth (IPC-IG), 2012)
[Introduction] Conditional Cash Transfer (CCT) programmes, including the Bolsa Família programme, have been extensively studied over recent years. The books, working papers and articles that have been written on the subject, if placed on top of each other, would pile up very high indeed. What excuse do I have for spending my time writing this one and asking you to spend yours reading it? My excuse is twofold. The first excuse is that, in spite of the aforementioned pile of studies, much about the programme is still not common knowledge. In the different forums in which I have been I have seen that many elementary facts about Bolsa Família are still relatively unknown to audiences beyond (some) Brazilian policymakers and government officials. How did the programme come about? What exactly was the Lula government's role in its creation? What impact has it had on poverty, inequality, education, health and labour supply? Did it have any significant political effects? What are its contradictions and possibilities for the future? My objective is to give brief and, if possible, conclusive answers to all these questions in a single text. My second excuse is timing. Brazil is at the end of an era. After eight years leading the country away from poverty and towards more equality, President Lula has passed the reins of power to his handpicked successor, the tough Dilma Roussef. Like any end of an era, it is also a time of new beginnings, and President Dilma has already declared that one of her main objectives is not the mere reduction of extreme poverty but its complete eradication. To this end, Bolsa Família will certainly be an important item in the policy toolkit and will consequently face some kind of changes. To tell the story as quickly as possible, I have divided this text into three parts. The first part is purely descriptive, telling the story of Bolsa Família's origin and going into the details of how it works. The second part tries to put the extensive literature on the programme's impacts into as few pages as possible. Finally, I argue that, in spite of its success, Bolsa Família must change, and discuss possibilities for the future.
Keywords: 330